Transforming practice, transforming practitioners: reflections on the TQFE in Scotland. Issue 1 (2nd January 2019) - Bain, Yvonne; Brosnan, Kevin; McGuigan, Aileen
ABSTRACT: This study offers reflections on the TQFE in Scotland as an example of the transformative professional learning model as identified by various authors. The focus of this study is the professional learning of lecturers in Scotland's colleges. Informed by wider considerations of teacher education more broadly, it will be of particular interest to those supporting a transformative model of professional learning in a variety of educational contexts. The research was undertaken as a collaborative initiative between each of the three universities which offer the TQFE in Scotland. Qualitative data are drawn from former TQFE participants and college mentors, and thematic analysis used to gain further insight from participant interviews. Findings highlight the transformative nature of the TQFE with an impact that is beyond the currency of the TQFE programme duration. The provision of transformative professional learning opportunities is now imperative given various pressures and tensions around the development of educators more generally and within contemporary Scottish Further Education in particular. Such pressures and tensions include: the varied demands within the Professional Standards for Lecturers in Scotland's Colleges, and the need for professional learning for college lecturers to go beyond a competency or tool-kit based approach and to be sustainable.